KOMPOSIT BAMBU SEBAGAI INOVASI MATERIAL DAN DESAIN AKSESORIS INTERIOR YANG BERBASIS GREEN DESIGN DAN BUDAYA DI SURAKARTA - Dhian Lestari Hastuti (Abdi Seni, 2020)
The issue of global warming consequences on the environment makes the interior designers look for an alternative of more sustainable materials and seek to reduce the waste in the production process. Bamboo and wood pieces of waste material is a material that can provide a solution when there is a material engineering effort between the two materials. Material engineering produces new material called composite. The material may be useful in the process of creation of the interior design, including interior accessories. Batik is chosen as the theme and concept of design creations of the interior accessories as reinforce cultural character with the concept of green design in Surakarta or Solo. The process of implementation of works is in partnership with a workshop production of Rempah Rumah Karya, so that the synergy between industry, practitioners, and academics can be properly implemented. Keywords: interior accessories, composite bamboo, batik, green design.